Isolation and diagnosis of Providencia rettgeri from different clinical cases and study - A. N., Hussein; A. A., AL-qalebi (Al-Qadisiyah Journal of Pure Science, 2018)
11 isolates were diagnosed followed to Providencia rettgeri of 750 swab collected from intensive care units and burns lobbies and operation room and Urosurgery unit ,also took swabs of medical devices and instruments used in hospitals in the city of Diwaniya, for the period from 1/2/2012 to 3/1/2013. Isolates were diagnosed depending on the microscopic and cultured characteristic directed and biochemical tests as well as the vitek system. Tested isolates were resistant direction 22 antibiotic commonly used to determine the resistance to these antibiotics as shown resistance to: 1- ÃŸâ€“lactamase antibiotics contained penicillins (Penicillin , Ampicillin , Amoxicillin andPipracillin) by 100% and cephalosporins (Cefotaxime, Ceftazidime and Cefalothin) by (81.8, 90.9 and 72.7) %respectively . 2- Aminoglygocides antibiotics (Gentamicin, Streptomycin, Tobramycin and Amikacin) by (100, 81, 90.9 and 100) % respectively. 3- Cholinergic antibiotics (Norflaxicin, Ciprofloxacin, and Ndidixacin) by (100, 63.6 and 100)% respectively. 4- (Tetracyclin and Chloramphenicol) by (100, 90.9) % respectively. 5- (Erythromycin, Trimethprim, Nitrofurantion and Rifampcin) by (81, 63.6, 90.9 and 72.7)%respectively. 6- Isolaties showed full sensitivity to Impinem (100%). Select the minimum inhibitory concentration for a number of antibiotics used (Cefatizidine, Cephalothine, Ampicilline and Amoxicillin) which colonies has grown in high concentrations of them micrograms (4-1024) Î¼g. ml-1.